Performance on sprint, agility and jump tests have moderate to strong correlations in youth football players but performance tests are weakly correlated to neuromuscular control tests - Sonesson, S.; Lindblom, H.; Hägglund, M. (Knee surgery, Sports Traumatology. Arthroscopy, 2020)
Purpose: This study aimed at evaluating the correlation between seven different performance tests and two neuromuscular control tests in youth football players and to evaluate the influence of sex and age groups on test results. Methods: One-hundred and fifteen football players (66 boys, 49 girls) mean age 14 ± 0.7 (range 13-16) years from youth teams were tested at the start of the second half of the competitive season. A test battery including agility t-test, 505 agility test, single-leg hop for distance test, side-hop test, countermovement jump test, 10-m sprint test, 20-m sprint test, tuck jump assessment (TJA) and drop vertical jump (DVJ) was completed. Results: Correlations between the seven different performance tests of agility, jump and sprint ability were generally moderate to strong (r = 0.534-0.971). DVJ did not correlate with the performance tests (rho = 0.004 to - 0.101) or with TJA total score (rho = 0.127). There were weak to moderate correlations between TJA total score and the performance tests (r = - 0.323-0.523). Boys performed better than girls in all performance tests (p < 0.001) and in TJA total score (p = 0.002). In boys, older players performed better than younger players in the majority of the tests, while there was no clear age influence among girls. Conclusion: Sprint performance was moderately to strongly correlated with agility and jump performance, and performance tests were weakly to moderately correlated to TJA, while DVJ did not correlate with the other tests. Boys performed better than girls on performance tests and TJA. An age effect on performance was evident in boys but not in girls.